1992
DOI: 10.1007/bf00917068
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between precorneal retention of viscous eye drops and tear fluid composition

Abstract: The influence of viscolysers on the precorneal residence of a fluorescent tracer was determined, using slit lamp fluorophotometry. The solution acceptability was evaluated by the volunteers by answering a standard questionnaire. The relationship between precorneal retention of viscous eye drops, discomfort and tear fluid composition after instillation of various cellulosic solutions was examined. Irritating hydroxypropylcellulose solution increases the total protein concentration of tears, without change in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Previous studies have shown differences in residency time of various demulcents on the ocular surface but provided little information on the efficacy of these substances. [13,14] The data in the present study show that these compounds do in fact appear to protect the cornea from drying. It was not possible, however, to statistically distinguish among these five products for efficacy compared to one another.…”
Section: Ubels Aupperlee and Meadows 278mentioning
confidence: 78%
“…Previous studies have shown differences in residency time of various demulcents on the ocular surface but provided little information on the efficacy of these substances. [13,14] The data in the present study show that these compounds do in fact appear to protect the cornea from drying. It was not possible, however, to statistically distinguish among these five products for efficacy compared to one another.…”
Section: Ubels Aupperlee and Meadows 278mentioning
confidence: 78%
“…An increase in concentration is accompanied by several side effects (cellular damage of corneal surface, possible toxic effects). The retention time can be improved by increasing the viscosity of the ocular solution (Ludwig et al, 1992), but these solutions induced a sticky feeling, troubled sight and increased blinking in human volunteers (Sintzel et al, 1996). Different methods to increase the penetration of the ocular drugs have been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Out of a few classifications of polymers, non-ionic have demonstrated the best mucoadhesive quality. [26,27] Release profile of HPMC 15cps grade is better compared to HPMC K100LV and HPMC K4M [ Figure 2]. …”
Section: Non-ionic Polymersmentioning
confidence: 99%